GENERATION Z SELF-DISCLOSURE ANALYSIS ON SECOND ACCOUNTS INSTAGRAM, TWITTER, AND TIKTOK (International Conference on Social and Islamic Studies, 2022)
Social media is not only used to share information and inspiration, but also for self-expression, "personal branding", and "vent" and even complaining, it is related to self-disclosure. Self-disclosure can occur if a person can open himself and various information about himself to others. This self-disclosure can be a variety of topics of information, behaviors, attitudes, feelings, desires, motivations, and ideas that are appropriate and contained in the person concerned. The second account has a consequence that makes oneself more introverted to others because it posts stories on the second account that are only followed by certain people more often than posting on the main account owned by generation Z on Instagram, Twitter, and Tiktok. The research method carried out by researchers uses qualitative research with a phenomenological approach. This research uses theory, Self Disclosure, New Media, Social Media, and Second Accounts. The subjects of this study were several users of the second account of Instagram, Twitter, and Tiktok generation Z. The object studied was the users of the second account of Instagram, Twitter, and Tiktok generation Z who experienced the phenomenon of self-disclosure. The primary data used by researchers is in the form of interviews and observations as data collection techniques. Secondary data in this study used book references, journals, and literature studies. The results of this study can be concluded that Generation Z can be more open and more able to express themselves in the second account compared to the first account, which makes its users feel safe.